PENGARUH LATIHAN DUMBBEL INCLINE PRESS TERHADAP HASIL TOLAK PELURU MAHASISWI KEPELATIHAN “B” ANGKATAN 2014 UNIVVERSITAS RIAU - Maria Riski; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :The problem in this research was the less of shot-put of students training “B” 2014 Riau University, until the time do shot-put got less maximal result. The design of this research was experiment design, the population of this research were students training “B” 2014 Riau University, the sampel of this research were 6 students, all of the population. The instrument of this research that used to find out shot-put result was shot-put test. After that, the data processed statistically, to try out the normality used liliefors test in significant taraf 0,05α. The hypotheses that proposes found there was effect of dumbble incline press practice forward shot-put result. Based on t-test analysis found that tcountamount 3,66 and ttable amount 2,015. It’s mean that tcount>ttable. Based on statistic data analysis found the average of pree-test was 5,175 and the average of post-test was 5,723, so the data was normal. The conclusion, there was a effect of dumbble incline press practice forward shot-put result of students training “B” 2014 Riau University Keyword: Dumbble incline press, shot-put result